2019
DOI: 10.1111/jce.14064
|View full text |Cite
|
Sign up to set email alerts
|

His bundle pacing, learning curve, procedure characteristics, safety, and feasibility: Insights from a large international observational study

Abstract: Background His‐bundle pacing (HBP) provides physiological ventricular activation. Observational studies have demonstrated the techniques’ feasibility; however, data have come from a limited number of centers. Objectives We set out to explore the contemporary global practice in HBP focusing on the learning curve, procedural characteristics, and outcomes. Methods This is a retrospective, multicenter observational study of patients undergoing attempted HBP at seven centers. Pacing indication, fluoroscopy time, HB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
98
7
14

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 148 publications
(121 citation statements)
references
References 17 publications
2
98
7
14
Order By: Relevance
“…The implantation technique is challenging with a longer learning curve. 38 HBP has low sensed R wave amplitude, which may result in atrial oversensing and ventricular undersensing. High pacing thresholds either at the time of implantation or during follow-up may result in early battery depletion and pulse generator change in 5%-10% of patients.…”
Section: Hbp Versus Lbbpmentioning
confidence: 99%
“…The implantation technique is challenging with a longer learning curve. 38 HBP has low sensed R wave amplitude, which may result in atrial oversensing and ventricular undersensing. High pacing thresholds either at the time of implantation or during follow-up may result in early battery depletion and pulse generator change in 5%-10% of patients.…”
Section: Hbp Versus Lbbpmentioning
confidence: 99%
“…A recent large multicentre study showed a mean FT 11.7 ± 12 minutes for HBP irrespective of the underlying rhythm. FT reduced with greater experience, plateauing after 30 to 50 cases 23 . We did not observe any significant difference in FT among different pacing indications, although subjects with SSS had 100% success and this is probably due to the small population.…”
Section: Discussionmentioning
confidence: 50%
“…FT reduced with greater experience, plateauing after 30 to 50 cases. 23 We did not observe any significant difference in FT among different pacing indications, although subjects with SSS had 100% success and this is probably due to the small population. Our data are in line with the results from Bhatt et al 22 where patients with more complex AV conduction disturbance had more prolonged procedure time.…”
Section: Discussionmentioning
confidence: 53%
“…High (approximately 7%) requirement for lead revision. 12,13 Backup ventricular leads may be indicated in case of sensing issues or for patient safety, resulting in more endovenous material, higher cost, and more complex programming. 11 Risk of compromise of lead function with AV node ablation (due to proximity of ablation site to pacing lead).…”
Section: Disadvantagesmentioning
confidence: 99%